Inhibition of MT1-MMP proteolytic function and ERK1/2 signalling influences cell migration and invasion through changes in MMP-2 and MMP-9 levels - Cepeda, Mario A.; Evered, Caitlin L.; Pelling, Jacob J. H .; Damjanovski, Sashko (Journal of cell communication and signaling, 2017)
Membrane type-1 matrix metalloproteinase (MT1-MMP, MMP-14) is a unique protease that cleaves extracellular proteins, activates proMMPs, and initiates intracellular signalling. MCF-7 cells are non-invasive and deficient in MT1-MMP, MMP-2, and MMP-9 expression. We created an MCF-7 cell line (C2) that stably produces active MT1-MMP and demonstrated increased ERK1/2 phosphorylation. MAPK inhibition in this cell line showed an inverse relationship in MMP-2 and MMP-9 transcripts where levels of these genes increased and decreased, respectively. Using invasive MDA-MB 231 cells that endogenously produce MT1-MMP and have naturally high pERK levels, we demonstrated the identical inverse relationship between MMP-2 and -9 transcript and protein levels, suggesting that this novel relationship is conserved amongst MT1-MMP positive breast cancer cells. To further analyze the relationship between MMP-2 and -9 levels, we chemically inhibited activation and catalytic activity of MT1-MMP using a furin and MMP inhibitor, respectively, to show that interference with the functions of MT1-MMP induced changes in MMP-2 and 9 transcript levels that were always inverse of each other, and likely mediated by differential transcriptional activity of the NF-κB transcription factor. Furthermore, we analyzed the functional consequences of these expression changes to show MMP, and in particular ERK, inhibition decreased migration and invasion using 2D culture, and inhibits the formation of an invasive phenotype in Matrigel 3D culture. This study demonstrated a novel inverse transcriptional relationship between MMP-2 and -9 levels and MT1-MMP activity that have functional consequences, and also showed that increases in the levels of MMPs does not necessarily correlate with an invasive phenotype.